2014
DOI: 10.4238/2014.march.24.26
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of MTHFR genetic polymorphisms as a possible etiology of male infertility

Abstract: ABSTRACT. The aim of this study was to explore the relationship between 2 genetic polymorphisms of the methylenetetrahydrofolate reductase gene (MTHFR), C677T and A1298C, and determine the long-term reproductive outcome in infertile men. This was a prospective study conducted in an andrology clinic. Men with a 1-year history of infertility were assessed for the MTHFR polymorphisms at a 5-year follow-up. We compared the MTHFR C677T and A1298C polymorphisms by polymerase chain reaction-restriction fragment lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…Moreover, Szczepańska et al (2011) opted to investigate women with endometriosis-associated infertility, and Settin et al (2011) studied those with unexplained pregnancy loss. Several studies carried out in different ethnicities regarding the C677T polymorphism in male infertility found a significant association (Aarabi et al, 2015;Kim et al, 2015;Li et al, 2014;Ni et al, 2015). Our study also found a positive association, but in regards to female infertility.…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, Szczepańska et al (2011) opted to investigate women with endometriosis-associated infertility, and Settin et al (2011) studied those with unexplained pregnancy loss. Several studies carried out in different ethnicities regarding the C677T polymorphism in male infertility found a significant association (Aarabi et al, 2015;Kim et al, 2015;Li et al, 2014;Ni et al, 2015). Our study also found a positive association, but in regards to female infertility.…”
Section: Discussionsupporting
confidence: 76%
“…An additional two publications contained duplicate data and were published by the same author; the one with the most subjects was included in the present analysis. Nine case-control studies considering 1,713 cases and 1,104 controls met the inclusion criteria[17–25](Fig 1). Of these, all 9 studies addressed the MTHFR C667T polymorphism; 3 studies addressed MTHFR A1298C polymorphism, and 3 studies addressed the MS A2756G polymorphism.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies showed similar association between the MTHFR-Ala222Val with male infertility in different populations. Some of these studies include the Indian (Singh et al, 2005), Korean (Lee et al, 2006;Park et al, 2005), Italian (Paracchini et al, 2006), Iranian (Karimian and Hosseinzadeh Colagar, 2014;Safarinejad et al, 2011), Chinese (Li et al, 2014;Zhou-Cun et al, 2007), and French (Ravel et al, 2009) populations. These results are consistent with four recent meta-analysis that report an association between 222Val allele with male infertility; especially in Asian populations (Gupta et al, 2011;Wei et al, 2012;Weiner et al, 2014;Wu et al, 2012).…”
Section: Discussionmentioning
confidence: 97%